Adjuvant effect of LPS and killed Propionibacterium acnes on the development of experimental gastrointestinal nematode infestation in sheep - Abel, L. C. J. [UNESP]; Chen, S. [UNESP]; Ricca, L. G. [UNESP]; Martins, M. F. [UNESP]; Garcia, M. [UNESP]; Ananias, R. Z.; Mussalem, J. S.; Squaiella, C. C.; Shaw, R. J.; Longo-Maugeri, I. M. (Wiley-Blackwell, 2009)
P>Gastrointestinal helminthic infection is an important worldwide sheep disease. The emergence of anthelminthic resistance has led to drives to seek new means of therapeutic control of helminthiasis in sheep. Several data demonstrated the adjuvant effect of Propionibacterium acnes on resistance to infection. Herein, we evaluate the adjuvant effect of the commercial suspension containing LPS and P. acnes on experimental helminthiasis. Sheep received three doses of LPS and P. acnes commercial suspension or saline 0 center dot 9% (control group). Both groups received orally Haemonchus contortus infective larvae on day 0. Parasitological, haematological, lymphoproliferation analysis, IL-5 and IgE determination were made once a week until 35th day after infection. Our results revealed increase on packed cell volumes on day 14, in LPS + P. acnes treated group. On 21st and 35th days after infection in the same group occurred increase on circulating eosinophils and lymphocytes, and also in the lymphoproliferative response to mitogen. On 35th day, the faecal eggs peak in LPS + P. acnes treated group was significantly lower than control. A negative correlation between faecal eggs counts and circulating eosinophils in the immunostimulant treated group was also observed. Our findings suggest that LPS + P. acnes suspension can be used as a strategy to control helminthiasis in sheep.
Keywords: helminthiasis; immunostimulant; lymphocytes; sheep